Midpoint of energy intake, non-fasting time and cardiorespiratory fitness in heart failure with preserved ejection fraction and obesity. (15th May 2022) - Billingsley, Hayley E.; Canada, Justin M.; Dixon, Dave L.; Kirkman, Danielle L.; Bohmke, Natalie; Rotelli, Brando; Kadariya, Dinesh; Markley, Roshanak; Van Tassell, Benjamin W.; Celi, Francesco S.; Abbate, Antonio; Carbone, Salvatore
Abstract: Background: Delayed time of evening meal is associated with favorable cardiorespiratory fitness (CRF) in patients with heart failure with preserved ejection fraction (HFpEF) and obesity. It is unknown, however, if increasing daily non-fasting time or delaying the midpoint of energy intake may also be associated with CRF. Objective: Our aim was to examine whether a longer non-fasting time, delayed midpoint of energy intake, or both, are associated with greater CRF in patients with HFpEF and obesity. Methods: We measured peak oxygen consumption (VO2 ), a measure of CRF, in 32 patients with HFpEF and obesity with cardiopulmonary exercise testing, and dietary intake using a five-pass 24-h dietary recall. Participants were divided into groups by having lesser (<11.6) or greater (≥11.6) periods of non-fasting time than the median and similarly, with earlier (<2:15 PM) or later (≥2:15 PM) than median midpoint of energy intake. Results: Median non-fasting time was 11.6 [10.6‐12.9] hours and midpoint of energy intake was 2:15 [1:04–3:00] PM. There were no differences in CRF between those with a shorter (<11.6) or longer (≥11.6) non-fasting time. Participants with a delayed midpoint of energy intake (≥2:15 PM) had greater peak VO2 and exercise time. Midpoint of energy intake ( r  = 0.444, P  = 0.011) and time of last meal ( r  = 0.550, P  = 0.001) displayed a positive association with peak VO2, but not non-fasting time nor time of first meal. Conclusions: Delaying the midpoint of energy intake by postponing last meal is associated with better peak VO2 and exercise time in patients with HFpEF and obesity. Highlights: In patients with HFpEF and obesity. Delayed midpoint of energy intake is associated with greater peak VO2 . This is driven by eating a delayed last meal, not eating the first meal earlier. Non-fasting time is not associated with cardiorespiratory fitness.